Halal Certification's Impact on Cassava Cracker UMKM's Growth in Raman Fajar Village - Al-Akbar, Fathul Falaah; Sholihah, Amanatus; Fahtimatuzzahroh, Diah; Ahmad, Fikri; Rohman, Khusnul Miftahur; Permana, Luna; Al-Abror, M. Abdul Malik; Rohman, M. Aulia; Nizar, M. Khoirun; Sidik, Syahrul; Azizah, Uswatun; Pratiwi, Wiwied (CV. BImbingan Belajar Assyfa, 2024)
This study examines the impact of halal certification implementation on business development and revenue increases for cassava cracker small and medium enterprises (SMEs) in Raman Fajar village. The research focuses on empowering the local community through guidance and training in obtaining business licenses and halal certification. The primary objective is to enable the community to achieve a better economic state and to serve as a form of student service through empowerment, training, counseling, mentoring, and exploring potential developments. The community service activities aim to ensure that all production stages, raw materials, and manufacturing processes comply with the established halal standards. Using a mixed-method approach, data were collected through interviews, surveys, and documentation involving 50 local businesses. The analysis revealed that the implementation of halal certification significantly enhanced consumer trust and opened new market opportunities for cassava cracker products. Quantitatively, there was a 30% increase in sales and a 25% expansion of the customer base following the certification. This study demonstrates a tangible contribution to business partners by providing halal certification and labels ready for packaging. The findings suggest that these efforts not only improve product competitiveness but also contribute to sustainable business growth in Raman Fajar village.